Consistency Rates Between Clinical Diagnoses Of Oral Lesions With Histopathological Reports - Mishra, Ravish; Kandel, Laxmi; Ali, Shahid; Kumar Singh, Sunil; Shubham, Snigdha (Birat Journal of Health Sciences, 2025)
Backgrounds : Accurate diagnosis is crucial for the effective management of oral lesions. This study aims to assess the consistency rates between clinical diagnoses and histopathological findings of various oral lesions encountered during clinical practices.Methodology: A retrospective analysis was conducted from 305 patients who had undergone biopsy in Department of Oral and Maxillofacial Surgery at UCMS College of Dental Surgery, Bhairahawa, Nepal between August 2020 to July 2023. Clinical diagnoses made by oral and maxillofacial surgeons were compared with the final histopathological results obtained from incisional or excisional biopsies. The consistency rate was calculated for each diagnostic category.Results: The overall agreement rate between clinical and histopathological diagnoses was found to be 69.83%. The highest consistency rate was observed in cases of mucoceles (94.4%), followed by fibromas (89.4%), radicular cyst (81%) and squamous cell carcinoma (81%). The lower agreement rate was seen in central giant cell granuloma (42.8%), followed by central ossifying fibroma (47%), dentigerous cysts (53.8%) and odontogenic keratocysts (54.1%).Conclusion : The findings of this study underscore the necessity for thorough clinical examinations and effective collaboration between clinicians and pathologists to enhance diagnostic accuracy and treatment outcomes. Regular clinicopathological meetings and continuous education programs may help improve the consistency between clinical and histopathological diagnoses.